The Impact of Prehospital Point of Care Ultrasounds on Emergency Patients Length of Stay in Thailand - Ienghong K; Cheung LW; Tiamkao S; Bhudhisawasdi V; Apiratwarakul K (Journal of Multidisciplinary Healthcare, 2023)
Kamonwon Ienghong,1 Lap Woon Cheung,2,3 Somsak Tiamkao,4 Vajarabhongsa Bhudhisawasdi,1 Korakot Apiratwarakul1 1Department of Emergency Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Accident & Emergency Department, Princess Margaret Hospital, Kowloon, Hong Kong; 3Emergency Medicine Unit, Li Ka Shing Faculty of Medicine, The University of Hong Kong, Pokfulam, Hong Kong; 4Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Korakot Apiratwarakul, Department of Emergency Medicine, Faculty of Medicine, Khon Kaen University, 123 Mittraphap Road, Mueang Khon Kaen District, Khon Kaen, 40002, Thailand, Tel +66 89 416 3663, Fax +66 43 366 870, Email Korakot@kku.ac.thPurpose: Globally, emergency departments (ED) are faced with an overcrowding problem. This issue is further compounded due to the multitude of contributing factors. Point of Care ultrasound (POCUS), especially when performed in prehospital care, that is before the patient is admitted to the ED has a high potential to reduce time of diagnosis and time of investigation which leads to shorter ED length of stay (LOS). The primary focus was on variances in ED LOS between the prehospital POCUS group and the standard care group.Patients and Methods: A cross-sectional study was conducted on prehospital patients who were admitted to the ED at Srinagarind Hospital, Thailand, from January to December 2021. We divided patients into two groups including patients who obtained prehospital POCUS (the prehospital POCUS group) and patients who received standard care treatment in which there was no prehospital POCUS performed (the standard care group). POCUS and ED medical records were documented and submitted for analysis.Results: Of 1348 prehospital patients, 840 were enrolled in this study: 169 with prehospital POCUS and 671 with standard care. Median LOS in the prehospital POCUS group was 159 min (IQR 89,289) versus 165 (IQR 102,330) in the standard care group (p = 0.125). Further imaging diagnostic test which affected ED LOS more than four hours was lower in the prehospital POCUS group (adjusted odds ratio [OR], 0.92; 95% confidence intervals [CI], 0.729– 1.666) than in the standard care group. The factor associated with increased odds of ED LOS more than four hour in the prehospital POCUS group was admission to hospital (adjusted OR 1.88; 95% CI, 1.230-2.239).Conclusion: Patients evaluated with prehospital POCUS had a shorter LOS than the only standard care treatment without statistical significance.Keywords: ultrasonography, prehospital emergency care, length of stay, emergency departments, crowding